Repaglinide, but Not Nateglinide Administered Supraspinally and Spinally Exerts an Anti-Diabetic Action in D-Glucose Fed and Streptozotocin-Treated Mouse Models - Sim, Yun-Beom (The Korean Physiological Society and The Korean Society of Pharmacology, 2013)
We have recently demonstrated that some anti-diabetic drugs such as biguanide and thizolidinediones administered centrally modulate the blood glucose level, suggesting that orally administered anti-diabetic drugs may modulate the blood glucose level by acting on central nervous system. The present study was designed to explore the possible action of another class of anti-diabetic drugs, glinidies, administered centrally on the blood glucose level in ICR mice. Mice were administered intracerebroventricularly (i.c.v.) or intrathecally (i.t.) with 5 to 30 µg of repaglinide or nateglinide in D-glucose-fed and streptozotocin (STZ)-treated models. We found that i.c.v. or i.t. injection with repaglinide dose-dependently attenuated the blood glucose level in D-glucose-fed model, whereas i.c.v. or i.t. injection with nateglinide showed no modulatory action on the blood glucose level in D-glucose-fed model. Furthermore, the effect of repaglinide administered i.c.v. or i.t. on the blood glucose level in STZ-treated model was studied. We found that repaglinide administered i.c.v. slightly enhanced the blood glucose level in STZ-treated model. On the other hand, i.t. injection with repaglinide attenuated the blood glucose level in STZ-treated model. The plasma insulin level was enhanced by repaglinide in D-glucose-fed model, but repaglinide did not affect the plasma insulin level in STZ-treated model. In addition, nateglinide did not alter the plasma insulin level in both D-glucose-fed and STZ-treated models. These results suggest that the anti-diabetic action of repaglinide appears to be, at least, mediated via the brain and the spinal cord as revealed in both D-glucose fed and STZ-treated models.